Decision-making for product design definition method in the early stage of design process of a successful new product - Alli, Hassan (Universiti Putra Malaysia Press, 2020)
Most product failure in the market is caused by the incompetence to integrate users’ requirements and preferences in the early stage of a new product development process. User involvement in the early stage of the design process is knowledgeable and opens possibilities for new product ideas, improves product innovation, decreases the product risks and prevents from irrelevant design. It also a pleasurable for the product developer to identify and verify the characteristics of a new product. This paper is evaluated on the decision-making process for the product definition phase of the product design and development stage, in which there is a need to incorporate the element of product design to establish the new product design characteristics. It extends the knowledge from product designers and users as a strategy for improving the efficiency of generating a new product idea and increases product quality and success in the market. Product Design Definition Method (PPDM) is explains the theory and procedure used in the decision making process. A very successful product is selected as a case study for validation in substantiating the significance of the method. The end of paper concluded the significant of method use for product designers in the product definition phase of product design and development stage that contributed to the success of a new product.